O Formato Das Tiras No Instagram E A Construção De Sentido (PERcursos Linguísticos, 2021)
From the historical perspective, the development of the comics was related to their medias and the comic strips were impacted by the market changes undertaken by newspapers. With the circulation of the comic strips in the several medias, we  questioned if the compositional format presented by them on the digital media interferes in the construction of meaning by the reader. This research considers the hypothesis that the comic strips formats interacts with textual processing and interferes with reader´s understanding and we adopted a concept of the multimodal text in a sociocognitive perspective. This paper examines two personal Instagram profiles with the aim of verifying how the compositional format of the comic strips interferes with the construction of meaning by the reader. We focus on comic strips adapted from the newspaper (printed media) and other published specifically on Instagram (digital media). The result showed that the reader creates reading expectations based on the format of the comic strips. The change of format interferes in textual  processing and enhances, or suppresses, the aspects that involve the reading of comics.Keywords: Comic strips. Text. Reading. Meaning. Social media.